Protecting human security in Africa - Abass, Ademola (ed); Abass, Ademola (Oxford ; New York, N.Y. : Oxford University Press, 2010)
This text explores the gravest threats to human security in Africa. Written by leading experts on its various themes, it combines legal and policy perspectives on the issues, making it an indispensable book for those seeking to learn more about the real challenges facing Africans and African organizations.
An Introduction to protecting human security in Africa / Ademola Abass -- Food security in Africa / Opeoluwa Badaru -- Environmental security in Africa / Ilias Bantekas -- Understanding the nexus between human security and small arms in Africa : the case of Ghana / Kwesi Aning -- The ILO and "human security" of sub-Saharan African labour / Ben Chigara -- Natural resource management and human security in Africa / Abiodun Alao -- Piracy off Somalia : the "emperors and the thieves of the oceans" in the 21st century / Efthymios Papastavridis -- Human security and the protection of refugees in Africa / Maria O'Sullivan -- Human rights of women in Africa : a prerequisite for human security / Manisuli Ssenyonjo -- Corruption as a threat to human security in Africa / Ebenezer Durojaye -- African peace and security architecture and the protection of human security / Ademola Abass -- The role of the human and peoples' rights section of the African Court of Justice and Human Rights / Gino J. Naldi -- African Commission on Human and Peoples' rights as a collective human security resource : promise, performance, and prospects / Obiora Chinedu Okafor -- The role of NGOs and civil society in advancing human security in Africa / Rachel Murray -- Future of human security in Africa / Ademola Abass.
Includes bibliographical references and index.
Keywords: Human rights -- Africa; Civil rights -- Africa; Human security -- Africa; Africa -- Social policy; Africa -- Social conditions -- 21st century